ANALISIS PENGGUNAAN MEDIA SOSIAL, POTONGAN HARGA DAN PELAYANAN PRIMA TERHADAP KEPUTUSAN PEMBELIAN TOKO RCK - Pratiwi, Aidha Bella; Wihara, Dhiyan Septa; Djoko, Edy (Universitas Nusantara PGRI Kediri, 2022)
The background of this research is that buying decision research needs to be done to find out how much influence the use of social media, discounted prices and excellent service have. So that it can be used to reach the target market and increase sales. This study uses a sample of 40 people who make up the whole population. The source of the data used is primary data obtained directly by giving questionnaires to buyers of Canon brand cameras at RCK Stores as respondents. This study uses a quantitative approach with multiple linear regression analysis method in SPSS for windows version 25. The conclusion of this research is (1) The use of social media partially has a significant effect on purchasing decisions of Canon brand cameras. (2) The partial price discount has a significant effect on purchasing decisions for Canon brand cameras. (3) Partially excellent service has no significant effect on purchasing decisions for Canon brand cameras. (4) The use of social media, discounted prices and excellent service simultaneously have a significant effect on purchasing decisions for Canon brand cameras.